Protected Areas of the New Millennium : for the Welfare of Local Community and Wildlife - Jha, Mohan (Indian Forester, 2002)
It is practically impossible to protect and manage the Protected Areas (PAs) in the country with the help of existing infrastructure and funds available to the Forest Department. Numbers of PAs are increasing at rapid speed every year. India has one of the world's most extensive networks of officially PAs , totalling 540 National Parks and Sanctuaries and covering over 4.5% forest area. Initially PAs were managed by excluding the local community and laws were framed accordingly. However , the results of such management have led to many conflicts and PAs suffer badly. Both PA managers and international conservation organizations should recognize that new management approaches are needed to build a more positive relationship with the people who live in and around PAs based on the facts that PAs are a complex ecosystem and the local communities are the integral part of the ecosystem.